Effects and safety of Ginkgo biloba on depression: a systematic review and meta-analysis - Lin, Jingya; Sun, Xiaojing; Yang, Lingli (Frontiers in Pharmacology, 2024)
Background：Since depression is one of the main factors contributing to the burden of disease throughout the world, we tried to analyze the effects and safety of Ginkgo biloba (GKB) on depression patients. Methods：We conducted literature search between January 2002 and May 2022 in 7 online databases (PubMed, Scopus, Embase, Google Scholar, Web of Sciences, Cochrane Library and China National Knowledge Infrastructure). A systematic literature review and meta-analysis was performed to compare effects and safety of GKB on depression patients, including subjective and objective indicators of depression evaluation. Results：Totally, 21 eligible articles with 9 indicators among 2074 patients were included. Several outcomes had difference and GKB group had better results than control group including Hamilton Depression Scale (HAMD) after taking GKB for 4 (MD=-2.86, 95%CI [-4.27, -1.46], P<0.01), 6 (mean difference (MD)=-3.36, 95%CI [-4.05, -2.67], P<0.01), and 8 (MD=-4.58, 95% CI [-6.11, -3.05], P<0.01) weeks, modified barthel index (MBI) (MD=14.86, 95%CI [12.07, 17.64], P<0.01), modified Edinburgh-Scandinavian stroke scale (MESSS) (MD=-4.57, 95%CI [-6.34, -2.79], P<0.01), brain-derived neurotrophic factor (BDNF) (MD=16.35, 95%CI [7.34, 25.36], P<0.01), 5-hydroxytryptamine (5-HT) (MD=4.57, 95%CI [3.08, 6.05], P<0.01) and clinical efficacy (RR=1.24, 95%CI [1.17, 1.32], P<0.01). However, there is no difference in adverse events between GKB and control. Conclusion：In conclusion, the main finding was GKB had better MBI, MESSS, BDNF, 5-HT and HAMD after 4, 6, 8 weeks than control group. GKB might reduce the risk of depression or depressive symptoms with safe clinical efficacy.